Acceptability patterns of hypothetic taxes on different types of foods in France - Florian Manneville; Barthélemy Sarda; Emmanuelle Kesse-Guyot; Sandrine Péneau; Bernard Srour; Julia Baudry; Benjamin Allès; Yann Le Bodo; Serge Hercberg; Mathilde Touvier; Chantal Julia (Public Health Nutrition)
Abstract